Perspectives on the Salon. Artists from Lviv in Paris in the first half of the 19th century - Świętosławska, Agnieszka (Ars inspiratio: Studies dedicated to Professor Eleonora Jedlińska, 2024)
In 1852, Henryk Rodakowski, a native of Lviv, was awarded a first prize at the Paris Salon, marking a significant achievement in the history of art. This was an unprecedented success; nevertheless, he was not the pioneering artist from Lviv to attempt to make a name for himself on the French art scene. The Lviv milieu had been experiencing a period of increasing activity since the beginning of this century, largely due to stronger contacts with other European centres. However, the dominant influence was that of the artistic centre of the Austrian Empire, Vienna. Paris was a city that was still relatively rarely visited by Lviv artists at that time. Nonetheless, these initial contacts were significant in terms of the transfer of trends and the awareness of the directions of development of contemporary painting. The objective of this article is to synthesise, often residual and incomplete, information on the interactions between artists from Lviv and the artistic milieu in France. The area of consideration will be both short-term visits and long-term stays, but above all this analysis will focus on the participation of these artists in the Salons, which, both for this text and for European artistic life, had a consolidating and centralising function for all artistic efforts.